Strategi Pembelajaran Langsung terhadap Keterampilan Dasar Menjahitpada Anak Disabilitas Rungu - Winie Angelina Putri; Dedy Ariyanto; Angger Timansah (JOEAI (Journal of Education and Instruction), 2026)
This study aims to analyze the effectiveness of direct instruction strategies in improving basic sewing skills in children with hearing impairments. The study used a Single Subject Research (SSR) method with an A-B design, comparing students' abilities in the baseline and intervention phases. The findings showed an improvement in sewing skills after the intervention, particularly in threading a needle and performing various basic stitches. Based on these results, it can be concluded that direct instruction strategies are an effective approach to developing basic sewing skills in children with hearing impairments.   Keywords: Deafness, Basic Sewing Skills, Direct Instruction Strategies